Clinical efficacy of sacubitril-valsartan combined with acute ST-segment elevation myocardial infarction after reperfusion: A systematic review and meta-analysis - Zhang, Dong; Wu, Hui; Liu, Di; Li, Yunzhao; Zhou, Gang; Yang, QingZhuo; Liu, YanFang (Frontiers in Cardiovascular Medicine, 2022)
Abstract：Background: Several studies have investigated the combined use of sacubitril- valsartan after reperfusion in acute ST-segment elevation myocardial infarction（STEMI）. However, the sample sizes of these studies were small and their results were somewhat heterogeneous. To determine the effect of sacubitril-valsartan on myocardial ischemia-reperfusion. Methods: Search PubMed, EMbase, Web of Science and The Cochrane Library, CNKI database, VIP database and Wanfang digital journal full-text database for eligible articles from their date of inception up to April , 2022. All data were meta-analyzed using Review Manager 5.3 and STATA 16.0 software.Results: A total of 23 studies including 2326 patients with acute ST-segment elevation myocardial infarction were included. These results of this meta-analysis indicated that left ventricular ejection fractions(LVEF) value within 6 months after surgery(odds ratio, 4.29; 95% confidence interval,3.78–4.80;P <0.00001), left ventricular end-diastolic diameter(LVEDD)value within 6 months after surgery(odds ratio,-3.11;95% confidence interval,-3.87–-2.35;P <0.00001) and left ventricular end-diastolic volume(LVEDV) value 6 months after operation(odds ratio,-6.22; 95% confidence interval, -7.10–-5.35; P <0.00001) are better than without sacubitril and valsartan.Conclusion: To sum up the above, the results of this study suggest that sacubitril- valsartan can reduce the reperfusion injury of ischemic myocardium by improving cardiac function within a follow-up period of 6 months.